Let the buyer beware: Content analysis of cosmetic surgery websites' provider information. (August 2019) - Goodman, J. Robyn
Given that many consumers do not understand any licensed physician can perform cosmetic surgery, cosmetic procedure advertising regulation is lacking and differs by state; and consumers often search for providers online and rely on the site's information. Cosmetic surgery websites have the potential to be a threat to consumers' safety and health. This study asked what types of physician information do cosmetic surgery websites supply. A content analysis was conducted with 873 physicians' information provided on cosmetic surgery websites in the top 10 cosmetic surgery cities, finding members of plastic surgery associations and core providers were more likely to list medical qualifications. All physicians were unlikely to list experience. Two-thirds stated their specific board certification, and 15% to 30% in each city failed to follow their state's regulations for disclosing board certification. The study concludes by suggesting national ethical guidelines.